ANALISIS KELAYAKAN BISNIS UMKM ROTI A KOTA PONTIANAK DITINJAU DARI ASPEK PEMASARAN DAN ASPEK MANAJEMEN - Safitri, Hendrika Vera; Basri, Muhammad; Kuswanti, Heni (Universitas Tanjungpura, 2025)
This study aims to assess the feasibility of the UMKM Roti A business in Pontianak City, focusing on marketing and management aspects. This study uses a qualitative approach with a case study method. The informants in this study were 8 people with data collection techniques using observation, interview and documentation techniques. The data analysis techniques used were data reduction, data presentation and conclusion drawing, with data validity testing using triangulation techniques and sources. The marketing aspect was assessed against the 7P marketing mix (product, price, place, promotion, people, process, physical evidence), while the management aspect assessed the ability of UMKM Roti A to manage its business with planning, organizing, actuating and controlling. The results of the study showed that overall UMKM Roti A was considered feasible by having a good marketing strategy such as products that have distinctive characteristics, affordable prices, strategic locations, effective promotions, and responsive services. However, there are several things that need to be improved such as store visibility, employee attitudes when busy and visual branding. From the management aspect, UMKM Roti A is considered feasible to be developed in the future. In terms of management, planning, actuating and controlling showed good results. However, in the organizing section, it is necessary to improve HR management for the future. Improvement of marketing and management efficiency for UMKM Roti A has the potential to develop in the future and be highly competitive.